The development and theoretical application of an implementation framework for dialectical behaviour therapy: a critical literature review - Gill Toms (Borderline Personality Disorder and Emotion Dysregulation, 2019)
Abstract Background Dialectical behaviour therapy (DBT) is a third wave behaviour therapy combining behaviour based components with elements of mindfulness. Although DBT effectiveness has been explored, relatively little attention has been given to its implementation. Frameworks are often the basis for gathering information about implementation and can also direct how the implementation of an intervention is conducted. Using existing implementation frameworks, this critical literature review scoped the DBT implementation literature to develop and refine a bespoke DBT implementation framework. Method and results The initial framework was developed by consolidating existing implementation frameworks and published guidance on DBT implementation. The critical literature review retrieved papers from Medline, CINAHL, PsycInfo, PubMed, and the reference lists of included papers. Framework elements were used as codes which were applied to the literature and guided the synthesis. Findings from the synthesis refined the framework. The critical literature review retrieved 60 papers but only 14 of these explicitly focused on implementation. The DBT implementation framework captured all the execution barriers and facilitators described in the literature. However, the evidence synthesis led to a more parsimonious framework as some elements (e.g., research and published guidance) were seldom discussed in DBT implementation. Conclusion To our knowledge this is the first published review exploring DBT implementation. The literature synthesis suggests some tentative recommendations which warrant further exploration. For instance, if DBT implementation is not pre-planned, having someone in the organisation who champions DBT can be advantageous. However, as the literature is limited and has methodological limitations, further prospective studies of DBT implementation are needed.